Bone Mass Loss and Sarcopenia in Ecuadorian Patients. (17th March 2020) - Intriago, M.; Maldonado, G.; Guerrero, R.; Messina, O. D.; Rios, C.
Abstract : Introduction . An intimate relationship between osteoporosis and sarcopenia has been established. At present, there are few epidemiological studies about osteosarcopenia due to the recent use of this term, especially in Latin America. Objective . To study the association between osteoporosis and sarcopenia and determine the prevalence of osteosarcopenia in patients who attended a rheumatology center in Ecuador. Methods . A cross-sectional study was conducted in a population of patients who had a densitometric study. The diagnosis of sarcopenia was determined by the DXA standard gold test, screening, and conventional methods (bioimpedance, anthropometric measurements, SARC-F, muscle function, and gait test). Results . A total of 92 patients were studied. The median age was 66 ± 10, 90% females. Using the criteria of SMI, 65% had sarcopenia of which 9% had only sarcopenia and 56% had osteosarcopenia; 22% had only osteopenia/osteoporosis; and 13% none of these conditions. The prevalence of sarcopenia according to handgrip strength was 60%, gait speed 45%, and SARC-F score 40%. The prevalence of osteosarcopenia according to handgrip strength was 51%, gait speed 34%, and SARC-F score 32%. Osteoporosis was associated with a higher prevalence of sarcopenia using the criteria of SMI since 40% had sarcopenia in the normal DXA group, 64% in the osteopenia group, and 76% in the osteoporosis group (p = 0.017 ). Of the women, 69% had sarcopenia compared to 33% of the men (p = 0.034 ). The BMI was lower in the group with sarcopenia (25.1 ± 4.1 kg/m 2 ) compared to the group without sarcopenia (29.4 ± 4.1 kg/m 2, p < 0.001 ). Patients with osteosarcopenia and sarcopenia had lower BMI, handgrip strength, ASM, SMI, and total-body skeletal muscle mass than those with osteopenia/osteoporosis or normal patients. Conclusion . 65% of the studied population had sarcopenia. It is clear that the prevalence of sarcopenia is higher in patients with greater loss of bone mass. Identifying pathways that affect both bone and muscle could facilitate the development of treatments that simultaneously improve osteoporosis and sarcopenia.